Synthesis, characterization and electrical properties of novel metal-free, Co(II), Cu(II), Fe(II), Mn(II), Sn(II) phthalocyanines peripherally tetra-substituted with 2,3-dihydro-1H-inden-5-yloxy moiety - ODABAŞ, ZAFER (ELSEVIER SCIENCE SA, 2011)
Novel metal-free and metal (Co, Cu, Fe, Mn and Sn) phthalocyanines were synthesized by cyclotetramerization of 4-(2,3-dihydro-1H-inden-5-yloxy)phthalonitrile and characterized by elemental analyses, IR, UV-vis and MALDI-TOF mass spectral data. The effect of metals or spectroscopic properties and aggregation behaviours of the novel Pcs were investigated in different concentration and solvents. Their electrical transport and dielectric properties were also investigated. The ac conductivity showed strong dependence on both temperature and frequency. The temperature dependence of frequency exponent s suggested a dominant hopping conduction process. It was observed that tan delta increases as the frequency increases and reaches a maximum and thereafter decreases. As the temperature increases the frequency at which tan delta reaches a maximum shifted towards higher frequencies. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Synthesis; Cyclotetramerization; Phthalocyanine; MALDI-TOF; Conductivity; GAS-SENSING PROPERTIES; AGGREGATION; DYNAMICS; MONO; ZN; CO